2018
DOI: 10.1177/1120672118803831
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of “IOL-Vip Revolution” telescopic intraocular lens in age-related macular degeneration cases with senile cataract

Abstract: Purpose: To evaluate the efficacy of the IOL-Vip Revolution telescopic intraocular lens in age-related macular degeneration patients. Methods: A total of 13 eyes of 12 age-related macular degeneration patients with senile cataract were enrolled. Selection of the patients was done by means of a low vision diagnostic and rehabilitative program (IOL-Vip software) that evaluates residual visual function. After standard phacoemulsification surgery, the incision site was enlarged and the IOL-Vip Revolution system wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“…A new study done by 2019 showed that 12 AMD patients with mean age 72.3 were enrolled, and BCVA pre-and post-operation were 1.08±0.14 and 0.81±0.16 log MAR and statistically significant between the difference (P=0.05) (25). Another noncomparative interventional case series (26) depicts the same improvements (the difference was 0.69 Log MAR), and the main best-corrected clinical gain was 44%.…”
Section: Iol-vip System (Intraocular Lens For Visually Impaired Peoplmentioning
confidence: 87%
See 3 more Smart Citations
“…A new study done by 2019 showed that 12 AMD patients with mean age 72.3 were enrolled, and BCVA pre-and post-operation were 1.08±0.14 and 0.81±0.16 log MAR and statistically significant between the difference (P=0.05) (25). Another noncomparative interventional case series (26) depicts the same improvements (the difference was 0.69 Log MAR), and the main best-corrected clinical gain was 44%.…”
Section: Iol-vip System (Intraocular Lens For Visually Impaired Peoplmentioning
confidence: 87%
“…In one study, they do the preoperative iridotomy in all other cases after noticing 3 of the first 5 cases developed a pupillary block with IOP increased (24). Although 1 article done by Dag et al (25) found that ACD was deeper post-operation from 2.7±0.3 to 3.1±0.7, the mean endothelium cell count was still significantly decreased postoperatively from 2,437±398 to 1,849±376, but lack of further information about the percentage among the subjects. Another study proved that endothelium cell loss appeared in 11.1% of subjects and 5.2% from 12 to 18 months (26).…”
Section: Iol-vip System (Intraocular Lens For Visually Impaired Peoplmentioning
confidence: 87%
See 2 more Smart Citations
“…A recent study by Dag et al reported using a telescopic intraocular lens in patients with advanced AMD. They observed that the parameter for difficulty with activities showed improvement (21).…”
Section: Discussionmentioning
confidence: 99%